SOME ASPECTS OF TAXATION IN THE DIGITAL ECONOMY: TAX ON GOOGLE IN UZBEKISTAN - Adhambek Bakhramovich Ismailov (International Engineering Journal For Research & Development, 2020)
In the past few years, due to the intensive development of information technology, a new industry has emerged - the digital economy, which includes the market for electronic services rendered to users remotely in an automated mode. At the same time, the digital economy is associated with major challenges for the international tax system[1]. Since these services have no tangible expression, it is difficult to provide a mechanism that would allow the collection of “import” value-added tax (VAT). Thus, it is necessary to take into account the change in the order of business organization and use modern international approaches in tax administration.